SUSTAINED RELEASE TABLETS OF SORAFENIB-SILIBININ COMBINATIONS FOR THE TREATMENT OF HEPATOCELLULAR CARCINOMA - Mishra, Savita; Hora, Sandhya; Shukla, Vibha; Das, Mukul; Kharkwal, Harsha; Katare, Deepshikha Pande (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to develop polymer coated sustained release tablet using sorafenib and silibinin combination for the treatment of hepatocellular carcinoma. Methods: The qualitative analysis such as weight variation, friability, hardness, interaction studies, disintegration and in vitro release were performed to validate formulated tablets. We have maintained the acceptable official limits for weight variation, friability, hardness and disintegration time according to prescribed pharmacopoeial recommendation. In vitro drug release studies were performed using USP-II (paddle type) dissolution apparatus. The MTT assay was performed for assessment of Cell viability of drug combination for tablet formulation. Molecular docking studies have been performed to determine the combinatorial mode of action for the tablet formulation. Results: Friability and weight variation were less than 1% for each formulation, which were within range of prescribed pharmacopoeial recommendation. The hardness of 20 tablets showed 5-6.5Kg/cm2 for all formulations 5-6.5Kg/cm2. The optimized formulation resulted in 98% drug release after 28 h. The present study reports the synergistic effects of drug combination to inhibit cell growth in HepG2 cell line. Molecular docking studies showed that sorafenib has high binding affinity for B-Raf vascular endothelial growth factor receptor Î² and protein kinase B. Silibinin showed binding affinity with MAP kinase-11, protein phosphatase 2 A and tankyrase. Conclusion: The present study reports for the first time a novel formulation for sustained release and reduced toxicity of sorafenib with enhanced inhibitory effect of the drug combination on cancerous hepatic cell line as well collaborative mechanism of action for the formulation.